Probabilistic seismic loss estimation by stochastic simulation algorithms - Cheung, Sai Hung (2014)
Prior estimation of losses in a structure due to future uncertain earthquakes, especially those which can lead to disastrous consequences, is essential to reduce potential losses and assist recovery. In this paper, we are particularly interested in the evaluation of seismic loss probability distribution including its tail by evaluating the seismic loss exceedance probability. Taking into account uncertainties from structural mod-eling, the modeling of future uncertain excitation and the models for damage and loss analysis, the evaluation of the exceedance probability will unavoidably involve the computation of high-dimensional integrals. A new method based on stochastic simulation algorithms is proposed to compute such integrals more efficiently. The effectiveness and efficiency of the proposed method are shown by an illustrative example involving a multi-storey inelastic building.